Gloria Church Cross - Mumbai Archive Project Team (Jio Institute, 2024)
Gloria Church Cross is a remnant of the former Gloria Church in Mazagon, located close to Hospital Lane. Constructed in 1548, the church began as a private chapel for Captain Antonio Passao and was demolished in 1596 to build a church in its place. This church was demolished and rebuilt in 1810. The site where Gloria Church and its parish house were located was designated for purchase for the Bombay Port Trust Railway. The old church was dismantled in 1910 after the Bombay Port Trust agreed to pay the Diocese two lakh rupees in compensation. Gloria Church in Byculla was reconstructed and reopened in 1913.